Bronchoscopic coil treatment for patients with severe emphysema: a meta-analysis - Slebos, Dirk-Jan; Hartman, Jorine E.; Klooster, Karin; Blaas, Stefan; Deslee, Gaetan; Gesierich, Wolfgang; Hetzel, Juergen; Hetzel, Martin; McNulty, William; Kemp, Samuel V.; Kessler, Romain; Leroy, Sylvie; et al. (Respiration, 2015)
Background: Bronchoscopic coil treatment has been shown to improve pulmonary function, exercise capacity, and quality of life in patients with severe emphysema. Objectives: To perform a meta-analysis of the results of four independent European clinical trials investigating this coil therapy for emphysema. Methods: Data on all patients included in the four European clinical trials were analyzed for efficacy and safety outcomes. Results: A total of 2,536 coils were placed during 259 procedures in 140 patients. A total of 37 chronic obstructive pulmonary disease exacerbations and 27 pneumonias were recorded as serious adverse events up to 1 year after treatment. The pneumothorax rate was 6.4%. Both 6 and 12 months after treatment, significant (all p < 0.001) improvements were observed for: forced expiratory volume in 1 s [+0.08 liters (±0.19) and +0.08 liters (±0.21)], residual volume [RV; -510 ml (±850) and -430 ml (±720)], 6-min walking distance [6MWD; +44.1 m (±69.8) and +38.1 m (±71.9)], and St. George's Respiratory Questionnaire score [SGRQ; -9.5 points (±14.3) and -7.7 points (±14.2)]. No differences in any outcome measures were observed between heterogeneous and homogeneous emphysema patients. Only a high baseline RV was found to be an independent predictor of successful treatment. Conclusions: Bronchoscopic coil treatment improves pulmonary function, 6MWD, and quality of life in patients with severe emphysema up to 1 year after treatment, independent of the distribution of the disease.
Gesehen am 18.06.2020